Political Institutionalization and Economic Rents: The Case of Turkey from 1923 to 1960 - Kalkan, Buğra (International Journal of Contemporary Economics and Administrative Sciences, 2017)
The theory of D. North, J. Wallis and B. Weingast (NWW), namely rational choice institutionalism, is applied here to Turkish history from 1923 to 1960. Economic rents are considered as the fundamental mechanisms to stop violence among the powerful groups in order to form a political unity in the emerging states/developing countries. It is asserted here that the Republic of Turkey created economic rents through economic interventionism and centrally planned economy during the mono-party regime years. Therefore, there are strict relations between the political institutionalization of Turkey as a mono-party regime and the interventionist economic policies of the Turkey from 1923 to 1950. The high scale of economic rents during the democratic era from 1950 to 1960 also undermined the political freedom in Tukey and destabilized the democratic political system.